EDUKASI PENCEGAHAN DAN PENANGANAN DAMPAK WABAH VIRUS CORONA (COVID-19) PADA MASYARAKAT KABUPATEN PEKALONGAN - AFIF TRI RAMADHANSYAH (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2021)
The impact of the corona virus outbreak is the weakening of the community's economic level due to restrictions on social interaction. So that people who implement their daily necessities from daily trading are greatly affected. On that basis, we organize the distribution of basic food packages to the less fortunate and provide information to reduce the risk of being infected or spreading COVID-19 by means of PHBS (Clean and Healthy Living Behavior). Wash your hands often with clean running water and soap, or an alcohol-based hand rub. Maintain a distance of at least 1 meter from people who are coughing or sneezing, when they cough or sneeze, people emit a splash from their nose or mouth and this splash can carry the virus. If you are too close to inhale the splash, you will catch the COVID-19 virus. Avoid touching the eyes, nose and mouth, when the hands touch various surfaces, the virus can be stuck on the hands. Contaminated hands can carry the virus to the eyes, nose or mouth, which are the entry points for the virus into the body.